2022
DOI: 10.1002/rth2.12815
|View full text |Cite
|
Sign up to set email alerts
|

Blocking domain 6 of high molecular weight kininogen to understand intrinsic clotting mechanisms

Abstract: Background The contact system is initiated by factor (F) XII activation and the assembly of high molecular weight kininogen (HK) with either FXI or prekallikrein (PK) on a negatively charged surface. Overactivation of this system contributes to thrombosis and inflammation in numerous diseases. To develop effective therapeutics for contact system disorders, a detailed understanding of this pathway is needed. Methods We performed coagulation assays in normal human plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…These data support a role for PKa in downstream intrinsic coagulation independent of FXII. 19 A study by Henderson et al examined protease:serpin complexes in the plasma from patients with COVID-19, to assess activation of the contact system and intrinsic pathway. 45 Levels of FXIa:serpin complexes and, to a lesser extent, PKa:C1 complexes were positively correlated with FIXa:AT level and it was thus suggested that both FXIa and PKa may contribute to FIX activation in vivo.…”
Section: Direct Activation Of Fix By Pka Results In Thrombin Generati...mentioning
confidence: 99%
See 3 more Smart Citations
“…These data support a role for PKa in downstream intrinsic coagulation independent of FXII. 19 A study by Henderson et al examined protease:serpin complexes in the plasma from patients with COVID-19, to assess activation of the contact system and intrinsic pathway. 45 Levels of FXIa:serpin complexes and, to a lesser extent, PKa:C1 complexes were positively correlated with FIXa:AT level and it was thus suggested that both FXIa and PKa may contribute to FIX activation in vivo.…”
Section: Direct Activation Of Fix By Pka Results In Thrombin Generati...mentioning
confidence: 99%
“…A recent study by Singh et al used an antibody “3E8” against domain 6 of HK, the binding site for both PK and FXI, which prevents binding of PK or FXI to HK. 19 Delayed clotting time in FXI-deficient plasma was prolonged further by the addition of 3E8, due to inhibition of PK activation, as PK-HK binding was prevented. The addition of PKa to FXI-deficient plasma in the presence of 3E8 and CTI (an inhibitor of FXIIa) significantly lessened the clotting delay, demonstrating a FXI- and FXII-independent role of PKa in clot formation.…”
Section: The History and The Current Understanding Of Pka Activation ...mentioning
confidence: 99%
See 2 more Smart Citations
“…1B). [31][32][33] During contact activation, FXIIa also converts factor XI (FXI), a homolog of PK, to factor XIa (FXIa; ►Fig. 1B).…”
Section: The Kallikrein-kinin System and Contact Activationmentioning
confidence: 99%